2015
DOI: 10.4236/ojn.2015.55052
|View full text |Cite
|
Sign up to set email alerts
|

Sense of Coherence in Persons with Dementia and Their Next of Kin—A Mixed-Method Study

Abstract: Indications of dementia disease include deterioration of memory, thinking, behaviour, and the ability to perform everyday activities. Any of these symptoms can lead to stress and difficulties organizing everyday life. As a way to view factors that support human health and well-being despite stressful situations, Antonovsky introduced a salutogenic model. This model proposes that sense of coherence primarily determines physical and mental health i.e. psychological well-being. Having a sense of coherence in ever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Other research on work-related SOC has also shown that a strong SOC is correlated with health-related quality of working life [38], high levels of work engagement [39,40] and less work-related stress [41]. SOC has successfully been incorporated into other qualitative studies, mainly in healthcare settings [42][43][44]. A recent systematic review provided evidence that a SOC helps to protect against a depressive state, burnout and job dissatisfaction among nurses, and that it is important to build a healthy work environment to foster the SOC [45].…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…Other research on work-related SOC has also shown that a strong SOC is correlated with health-related quality of working life [38], high levels of work engagement [39,40] and less work-related stress [41]. SOC has successfully been incorporated into other qualitative studies, mainly in healthcare settings [42][43][44]. A recent systematic review provided evidence that a SOC helps to protect against a depressive state, burnout and job dissatisfaction among nurses, and that it is important to build a healthy work environment to foster the SOC [45].…”
Section: Conceptual Frameworkmentioning
confidence: 99%